Efficacy and Safety of Percutaneous Nephrolithotomy versus Ureteroscopy for Pediatric Kidney Stone Management: A Systematic Review and Meta-Analysis - Gilang Samudero; Jeremi Geraldy Widodo (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2026)
Introduction. Percutaneous Nephrolithotomy (PCNL) and ureteroscopy are surgical options performed in children with kidney and/or ureteral calculi, despite no differences in stone clearance. Percutaneous nephrolithotomy was reported to have a high Stone Free Rate (SFR) for paediatric patients. The use of ureteroscopy in children has increased with high ureteral and kidney Stone-Free Rate (SFR) and low complication rate. The safety of PCNL and ureteroscopy is assessed by the complaints of patients. The study aims to comprehend the efficacy and safety of percutaneous nephrolithotomy and ureteroscopy procedures for paediatric kidney stone management. Methods. A systematic search was carried out following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). Multiple databases, including Medscape, Science Direct, and ProQuest, were systematically searched for relevant articles. Relevant parameters explored using Review Manager V5.4.1. Results. Three prospective and two retrospective comparative studies involving a total of 1443 renal units, with 209 cases done using PCNL and 1229 cases using ureteroscopy. There was no significant difference in stone-free rate and sepsis between these two groups of patients (OR: 0,89; 95% CI: 0,59-1,35; P=0,58 and OR: 0,34; 95% CI: 0,04-3,13; P=0,97, respectively). The risk of fever and hematuria was significantly lower in patients treated with ureteroscopy compared to PCNL (OR: 2,41; 95% CI: 1,07-5.46; P=0.04 and OR: 17,93; 95% CI: 2,28-140,93; P=0,006, respectively). Conclusion. The analysis found that PCNL has a similar SFR compared to ureteroscopy. The risk of fever and hematuria was significantly lower in patients treated with ureteroscopy compared to PCNL. Further randomized clinical trials are required to compare the safety and efficacy of PCNL versus ureteroscopy for pediatric kidney stone management.